High-performance copper-chromium-zirconium alloy cast rod and wire rod and preparation method thereof

Through vacuum continuous casting technology and "pull + stop + retreat" traction method, the problems of Cu-Cr-Zr alloy failure in industrial production and low casting rod quality are solved, and high quality and uniform casting rods are achieved The production meets the requirements of application performance.

CN119464799AActive Publication Date: 2025-02-18JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411484292.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

Cu-Cr-Zr alloys have problems such as failure in traction or low quality of cast rods in industrial production, especially due to the increased viscosity of Zr elements, the resistance of continuous casting of copper alloys under vacuum, making it difficult to ensure uniformity and high cast rods. quality.

Method used

Using vacuum continuous casting technology, add elements such as Mg or Zn in an inert gas atmosphere to improve the viscosity of the copper liquid, and use the "pull + stop + retreat" traction method to avoid breaking of the casting rod during the downward traction process. Or thermal cracking occurs.

Benefits of technology

The high-quality and industrial production of Cu-Cr-Zr alloy is achieved, ensuring uniform structure of the cast rod, small grains, high tensile strength and conductivity, and meeting the application performance requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464799A_ABST
    Figure CN119464799A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance copper-chromium-zirconium alloy cast rod and wire and a preparation method thereof, and relates to the field of metal material processing. The alloy casting rod comprises Cr, Zr, R and the balance copper and inevitable impurities, the R is Mg and / or Zn and other elements, cathode copper, a copper-chromium intermediate alloy, a copper-zirconium intermediate alloy, a copper-magnesium intermediate alloy and / or a copper-zinc intermediate alloy are completely melted and then subjected to heat preservation treatment, then vacuum down-drawing continuous casting is conducted, traction is conducted in the mode of'traction, stopping and withdrawing ', and the casting rod is obtained. The casting rod is produced through vacuum down-drawing continuous casting, high-quality and industrial production can be achieved, the viscosity of molten copper is effectively improved by adding elements such as Mg or Zn, the resistance of copper alloy down-drawing continuous casting is reduced, meanwhile, the situation that the casting rod is broken or hot cracks are generated in the down-drawing process is avoided in cooperation with the traction mode of'traction + stop + retreat ', and the production efficiency is improved. The finally prepared casting rod is uniform in structure and small in grain, good mechanical performance and machinability are obtained, and the application performance requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material processing, and in particular to a high-performance copper-chromium-zirconium alloy casting rod and wire and a preparation method thereof. Background Art

[0002] Cu-Cr-Zr alloy is a typical structural and functional integrated material. It is a precipitation-strengthened alloy containing a large amount of metastable Cr-rich precipitate phase. Due to its high strength and good electrical and thermal conductivity, it is often used in electronic power, aircraft carriers, aerospace, mechanical transportation and national defense, such as electrified railway contact wires, large-scale integrated circuit lead frames, aircraft carriers and spacecraft conductive devices, as well as military communication conductive cables and aviation cables. Due to the high affinity of Cr and Zr elements with oxygen, the alloy is prone to burnout during smelting, and large-scale continuous production is impossible, and the performance is unstable. Industrial production often uses non-vacuum upward continuous casting to prepare copper-chromium-zirconium alloy casting rods. It is difficult to ensure uniform organizational structure and excellent surface quality of the casting rods prepared by this method even if the process parameters are strictly controlled.

[0003] Vacuum melting can solve this kind of problem very well. Vacuum melting mainly includes vacuum induction melting, vacuum downcasting, vacuum horizontal continuous casting and directional solidification. Although vacuum induction melting technology is simple and easy to operate, it can only be used for small batch casting experiments, and it is difficult to carry out process production. Directional solidification technology is not suitable for industrial production. Downcasting and horizontal continuous casting can both be used for industrial production. Relatively speaking, the casting rods prepared by downcasting are of better quality and more conducive to the preparation of fine wires.

[0004] In view of the current performance of Cu-Cr-Zr alloy fine wire after tubular annealing (tensile strength ≥ 480MPa, conductivity ≥ 78% IACS, elongation after annealing ≥ 8%), it is necessary to draw the wire to a wire diameter of 0.16mm, and its hard tensile strength ≥ 700MPa, conductivity ≥ 70% IACS, and the use length ≥ 1500m. However, the presence of Zr element in Cu-Cr-Zr alloy will significantly increase the viscosity of copper solution, which increases the resistance of vacuum continuous casting of copper alloy, which is easy to cause traction failure. It is urgent to develop a Cu-Cr-Zr alloy casting rod production technology that can be semi-continuously produced and of good quality to meet production needs. Summary of the invention

[0005] The invention provides a high-performance copper-chromium-zirconium alloy casting rod and wire and a preparation method thereof, which are used to produce a Cu-Cr-Zr alloy that is easy to oxidize and segregate, and solve the problems of traction failure or insufficient casting rod quality in the current industrial production of Cu-Cr-Zr alloy.

[0006] In order to solve the above technical problems, one of the purposes of the present invention is to provide a method for preparing a high-performance copper-chromium-zirconium alloy casting rod, wherein the alloy casting rod comprises 0.2wt%-1.5wt% Cr, 0.02wt%-0.15wt% Zr and 0.01wt%-0.05wt% R, and the balance is copper and unavoidable impurities, wherein R is Mg and / or Zn, and the preparation method comprises the following steps:

[0007] (1) Under inert gas atmosphere, after the cathode copper, copper-chromium master alloy and copper-zirconium master alloy are melted, copper-magnesium master alloy and / or copper-zinc master alloy are added, and after they are completely melted, electromagnetic stirring is performed, a covering agent is added, and the copper liquid is heat-insulated;

[0008] (2) Carry out vacuum continuous casting, turn on the cooling water and air cooling device at the outlet of the traction pipe, turn on the traction system and the wire-retracting device, and the whole process is carried out in a "traction + stop + retreat" mode, with a stop time of 0.1-0.2s, a stop-pull time ratio of more than 3:1, and a stop-retreat time ratio of more than 5:1. In the initial stage, the traction is carried out at a speed of 3mm / s for 50-200mm, and then increased to 5-7mm / s for traction, and the retreat speed is kept unchanged at 2mm / s. The copper liquid condenses into a solid in the crystallizer, and the traction is stable until the traction is completed to obtain a cast rod.

[0009] By adopting the above scheme, the present application produces cast rods through vacuum downward continuous casting, which can realize industrial production. The vacuum oxygen-isolating environment can prevent the Cr and Zr elements in the copper-chromium-zirconium alloy from undergoing oxidation reactions with oxygen to affect the purity and performance of the alloy. At the same time, the cast rods produced by vacuum downward continuous casting have higher quality than those produced by vacuum horizontal continuous casting. Since the presence of Zr in the alloy will significantly increase the viscosity of the copper solution, the present application can effectively improve the viscosity of the copper liquid by adding elements such as Mg or Zn to the copper-chromium-zirconium alloy, thereby reducing the resistance of the copper alloy downward continuous casting. At the same time, the "pull + stop + retreat" traction method can be used to prevent the cast rods from breaking or thermal cracking during the downward traction process, and trace elements such as Mg and Zn have little effect on the mechanical and electrical conductivity of the alloy. The cast rods finally prepared have uniform organizational structure and small grains, high tensile strength and electrical conductivity, good mechanical properties and machinability, and can meet application performance requirements.

[0010] As a preferred embodiment, in step (1), under inert gas atmosphere, cathode copper is added and melted at above 1050°C, then inert gas protection is introduced, copper-chromium master alloy is added, the temperature is raised to 1150-1250°C, copper-zirconium master alloy is added, the temperature is raised to 1250-1350°C, copper-magnesium master alloy and / or copper-zinc master alloy is added, electromagnetic stirring is performed after complete melting, covering agent is added, and the temperature is kept at 1200-1300°C for 10-30 minutes.

[0011] By adopting the above scheme, the present invention adopts the method of adding different master alloys in sequence, and melting the different master alloys at a specific temperature, and simultaneously performing electromagnetic stirring, which can effectively prevent component segregation, make the cast rod structure more uniform, and refine the grains.

[0012] As a preferred embodiment, in step (1), the covering agent is cryolite.

[0013] As a preferred embodiment, in step (2), the crucible and crystallizer used for vacuum continuous casting are independent of each other and are internally sprayed with boron nitride coating, embedded with 5-10 mm boron nitride or embedded with 5-10 mm high-purity molybdenum-titanium alloy.

[0014] By adopting the above scheme, the present invention uses boron nitride treatment on the crucible and the crystallizer, which ensures good heat conduction and can effectively prevent the two elements Cr and Zr from reacting with graphite to form intermetallic compounds, thereby causing uneven composition. It also reduces the friction of the molten metal when entering the crystallizer, which is beneficial to the implementation of the traction process and reduces the problems of rough surface and easy fracture of the casting rod.

[0015] As a preferred solution, in step (2), the pressure of the vacuum continuous casting is less than 0.1 Pa.

[0016] As a preferred embodiment, in step (2), the diameter of the graphite crystallizer is 12.5-16 mm.

[0017] As a preferred solution, in step (2), the water flow rate of the cooling device is 500-4000 L / h, and the circulating water temperature is 25-30°C.

[0018] In order to solve the above technical problems, a second object of the present invention is to provide a high-performance copper-chromium-zirconium alloy casting rod.

[0019] In order to solve the above technical problems, the third object of the present invention is to provide a method for preparing a high-performance copper-chromium-zirconium alloy wire, comprising the following steps:

[0020] (1) continuously extruding the cast rod to 6-10 mm at an extrusion temperature of 600-800° C., and then continuously drawing the extruded rod for the first time to 2-4 mm at a drawing rate of 17-34 m / min to obtain a wire blank;

[0021] (2) The wire blank is heat treated at a temperature of 450-600° C. After cooling, it is continuously drawn for a second time to 0.1-0.2 mm at a drawing speed of 300-500 m / min to obtain a wire.

[0022] As a preferred embodiment, in step (1), continuous extrusion is performed using a preheated pure copper rod as a lead, the preheating temperature of the pure copper extrusion lead is 350-500°C, the extrusion temperature is 600-800°C, the extrusion wheel speed is 6-10 rpm, and the gap between the extrusion wheel and the die cavity is controlled to be 0.3-0.6.

[0023] In order to solve the above technical problems, a fourth object of the present invention is to provide a high-performance copper-chromium-zirconium alloy wire.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present application produces cast rods by vacuum downward continuous casting, which can achieve high-quality and industrialized production. Vacuum oxygen isolation can prevent oxidation reactions of Cr and Zr elements that affect the purity and performance of the alloy. Adding elements such as Mg or Zn can effectively improve the viscosity of molten copper and reduce the resistance of downward continuous casting of copper alloys. At the same time, the "pull + stop + retreat" traction method is used to prevent the cast rods from breaking or hot cracking during the downward traction process. The cast rods finally prepared have uniform organizational structure and small grains, and obtain good mechanical properties and machinability, which can meet the application performance requirements.

[0026] 2. The present invention adopts the method of adding different master alloys in sequence, and the different master alloys need to be melted at a specific temperature, and electromagnetic stirring is performed at the same time, which can effectively prevent component segregation, make the cast rod structure more uniform, and refine the grains.

[0027] 3. The present invention uses boron nitride treatment on the crucible and the crystallizer, which not only ensures good heat conduction, but also effectively prevents the two elements Cr and Zr from reacting with graphite to form intermetallic compounds, and also reduces the friction of the molten metal when entering the crystallizer, which is beneficial to the implementation of the traction process and reduces the problems of rough surface and easy fracture of the casting rod. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 : A schematic diagram of the structure of a graphite crucible used in the present invention;

[0029] Figure 2 : A schematic diagram of the structure of a graphite crystallizer used in the present invention;

[0030] Figure 3 : Crystal images of cast rods obtained in step (2) of the preparation method of Example 1 and Comparative Example 1 of the present invention, and traction conditions of cast rods prepared in Comparative Examples 1-2 (Note: a-crystal image of the cast rod of Example 1; b-crystal image of the cast rod of Comparative Example 1; c-cast rod with thermal cracks produced by traction in Comparative Example 2; d-cast rod without thermal cracks successfully pulled in Example 1). DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The vacuum downcasting equipment for copper-chromium-zirconium alloy in the present application includes a melting vacuum system, a molten metal insulation system, a downcasting system and other auxiliary systems. The downcasting system includes a graphite crucible, a vacuum induction heating device, a circulating water cooling system, a graphite crystallizer and a traction device containing a dummy rod. The structure of the graphite crucible is as follows: Figure 1 As shown in the figure, the selection of a crucible with a 0.5 mm boron nitride insert can effectively prevent the two elements Cr and Zr from reacting with graphite to form intermetallic compounds and causing uneven composition, and also prevent the friction of the molten metal from increasing when entering the crystallizer, which is not conducive to the implementation of the traction process. The structure of the graphite crystallizer is shown in the figure. Figure 2 As shown, the graphite crystallizer adopts internal spraying of boron nitride coating for traction, with a diameter of 12.5-16mm, which ensures good heat conduction, reduces traction resistance, and reduces the occurrence of problems such as rough surface and easy fracture of the cast rod.

[0033] Example 1

[0034] A high-performance copper-chromium-zirconium alloy wire comprises 0.5wt% Cr, 0.05wt% Zr, 0.05wt% Mg, the balance is copper, and the wire diameter is 0.16mm. The preparation method thereof comprises the following steps:

[0035] (1) Cathode copper (purity 99.99%), Cu10Cr master alloy (10wt% Cr, impurity content ≤0.1%), Cu40Zr (40wt% Cr, impurity content ≤0.1%) and Cu5Mg (5wt% Mg, impurity content ≤0.1%) master alloy were prepared according to alloy composition, wherein Cr and Zr elements were added according to a 25% burn-off ratio, Mg element was added according to a 40% burn-off ratio, and the burn-off ratio of cathode copper was calculated as 3%, and vacuum was drawn to 4×10 -2 Pa, first heat to above 1080℃ to melt the cathode copper, then introduce an appropriate amount of argon gas for protection, then add Cu10Cr master alloy, continue to introduce argon gas until the pressure in the furnace is equivalent to atmospheric pressure, heat to 1200℃ and add Cu40Zr master alloy, then heat to 1300℃ and add Cu5Mg master alloy, after the master alloy is completely melted, perform electromagnetic stirring, add cryolite as a covering agent, keep warm at 1280℃ for 20 minutes, so that the solution can be fully diffused;

[0036] (2) Vacuum downward continuous casting is carried out with a pressure of less than 0.1Pa. The molten steel is injected vertically downward into the crystallizer placed below. The cast rod moves downward. The cooling water and air cooling device at the outlet of the traction pipe are turned on with a flow rate of 800L / h. The water tank temperature is maintained at 28±2℃. The traction system and the wire-retracting device are turned on. The whole process is carried out in a "traction + stop + retreat" manner. The stop time is 0.1s, the stop-pull time ratio is 3:1, and the stop-retreat time ratio is 5:1. In the initial stage, 100mm is pulled at a speed of 3mm / s, and then the traction speed is increased to 5mm / s. The retreat speed is maintained at 2mm / s. The copper liquid condenses into a solid in the graphite crystallizer. The traction is stable until the traction is completed, and a high-quality cast rod with a wire diameter of 16mm is obtained without thermal cracking or fracture.

[0037] (3) The obtained 16 mm cast rod is continuously extruded, and a preheated pure copper rod is used as a guide for extrusion. The pure copper extrusion guide is preheated at 400 ° C for 3 h, the extrusion temperature is 700 ° C, the extrusion wheel speed is 7 rpm, and the gap between the extrusion wheel and the die cavity is controlled at 0.5 mm. The cast rod is extruded from a wire diameter of 16 mm to 8 mm, and then the extruded rod is pulled to a wire diameter of 2.6 mm by continuous drawing technology. As the wire diameter decreases, the drawing rate gradually increases from 17 m / min to 34 m / min;

[0038] (4) The wire billet with a wire diameter of 2.6 mm was placed in a gas quenching furnace for heat treatment. The heat treatment process was carried out at 500°C for 6 hours and then cooled in the furnace. The semi-soft wire billet was subsequently continuously drawn at a drawing speed of 400 m / min to obtain a 0.16 mm wire.

[0039] Example 2

[0040] A high-performance copper-chromium-zirconium alloy wire comprises 1wt% Cr, 0.2wt% Zr, 0.05wt% Zn, the balance is copper, and the wire diameter is 0.16mm. The preparation method thereof comprises the following steps:

[0041] (1) Cathode copper (purity 99.99%), Cu10Cr master alloy (10wt% Cr, impurity content ≤0.1%), Cu40Zr (40wt% Cr, impurity content ≤0.1%) and Cu10Zn (10wt% Zn, impurity content ≤0.1%) master alloy were prepared according to alloy composition, wherein Cr and Zr elements were added according to a 25% burn-off ratio, Zn element was added according to a 30% burn-off ratio, and the burn-off ratio of cathode copper was calculated as 3%, and vacuum was drawn to 4×10 -2Pa, first heat to above 1080℃ to melt the cathode copper, then introduce an appropriate amount of argon gas for protection, then add the Cu10Cr master alloy, continue to introduce argon gas until the pressure in the furnace is equivalent to the atmospheric pressure, heat to 1150℃ and add the Cu40Zr master alloy, then heat to 1250℃ and add the Cu10Zn master alloy, after the master alloy is completely melted, perform electromagnetic stirring, add cryolite as a covering agent, and keep at 1250℃ for 30 minutes to allow the solution to fully diffuse;

[0042] (2) Vacuum continuous casting was carried out with a pressure of less than 0.1 Pa. The cooling water and air cooling device at the outlet of the traction pipe were turned on with a flow rate of 2000 L / h. The water tank temperature was maintained at 28±2°C. The traction system and the wire-retracting device were turned on. The whole process was carried out in a "traction + stop + retraction" mode with a stop time of 0.1 s, a stop-pull time ratio of 4:1, and a stop-retraction time ratio of 5:1. In the initial stage, 100 mm was pulled at a speed of 3 mm / s, and then the traction speed was increased to 7 mm / s. The retraction speed was kept constant at 2 mm / s. The copper liquid condensed into a solid in the graphite crystallizer. The traction was stabilized until the traction was completed, and a high-quality cast rod with a wire diameter of 16 mm was obtained without thermal cracking or fracture.

[0043] (3) The obtained 16 mm cast rod is continuously extruded, and a preheated pure copper rod is used as a guide for extrusion. The pure copper extrusion guide used is preheated at 380°C for 4 hours, the extrusion temperature is 600°C, the extrusion wheel speed is 6 rpm, and the gap between the extrusion wheel and the die cavity is controlled at 0.5 mm. The cast rod is extruded from a wire diameter of 16 mm to 8 mm, and then the extruded rod is pulled to a wire diameter of 2.6 mm by continuous drawing technology. As the wire diameter decreases, the drawing rate gradually increases from 17 m / min to 34 m / min;

[0044] (4) The wire billet with a wire diameter of 2.6 mm was placed in a gas quenching furnace for heat treatment. The heat treatment process was carried out at 550°C for 5 hours and then cooled in the furnace. The semi-soft wire billet was subsequently continuously drawn at a drawing speed of 400 m / min to obtain a 0.16 mm wire.

[0045] Example 3

[0046] A high-performance copper-chromium-zirconium alloy wire comprises 0.8wt% Cr, 0.1wt% Zr, 0.03wt% Mg, the balance is copper, and the wire diameter is 0.16mm. The preparation method thereof comprises the following steps:

[0047] (1) Cathode copper (purity 99.99%), Cu10Cr master alloy (10wt% Cr, impurity content ≤0.1%), Cu40Zr (40wt% Cr, impurity content ≤0.1%) and Cu5Mg (5wt% Mg, impurity content ≤0.1%) master alloy were prepared according to alloy composition, wherein Cr and Zr elements were added according to a 25% burn-off ratio, Mg element was added according to a 40% burn-off ratio, and the burn-off ratio of cathode copper was calculated as 3%, and vacuum was drawn to 4×10 -2 Pa, first heat to above 1080℃ to melt the cathode copper, then introduce an appropriate amount of argon gas for protection, then add Cu10Cr master alloy, continue to introduce argon gas until the pressure in the furnace is equivalent to atmospheric pressure, heat to 1200℃ and add Cu40Zr master alloy, then heat to 1250℃ and add Cu5Mg master alloy, after the master alloy is completely melted, perform electromagnetic stirring, add cryolite as a covering agent, keep warm at 1250℃ for 20 minutes to allow the solution to fully diffuse;

[0048] (2) Vacuum continuous casting was carried out with a pressure of less than 0.1 Pa. The cooling water and air cooling device at the outlet of the traction pipe were turned on with a flow rate of 3000 L / h. The water tank temperature was maintained at 28±2°C. The traction system and the wire-retracting device were turned on. The whole process was carried out in a "traction + stop + retraction" mode with a stop time of 0.2 s, a stop-pull time ratio of 3:1, and a stop-retraction time ratio of 5:1. In the initial stage, 100 mm was pulled at a speed of 3 mm / s, and then the traction speed was increased to 6 mm / s. The retraction speed was kept constant at 2 mm / s. The copper liquid condensed into a solid in the graphite crystallizer. The traction was stabilized until the traction was completed, and a high-quality cast rod with a wire diameter of 12.5 mm was obtained without thermal cracking or fracture.

[0049] (3) The obtained 12.5 mm cast rod is continuously extruded, and a preheated pure copper rod is used as a guide for extrusion. The pure copper extrusion guide used is preheated at 450°C for 10 hours, the extrusion temperature is 800°C, the extrusion wheel speed is 7 rpm, and the gap between the extrusion wheel and the die cavity is controlled at 0.5 mm. The cast rod is extruded from a wire diameter of 12.5 mm to 8 mm, and then the extruded rod is pulled to a wire diameter of 2.6 mm by continuous drawing technology. As the wire diameter decreases, the drawing rate gradually increases from 17 m / min to 34 m / min;

[0050] (4) The wire billet with a wire diameter of 2.6 mm was placed in a gas quenching furnace for heat treatment. The heat treatment process was carried out at 500°C for 6 hours and then cooled in the furnace. The semi-soft wire billet was subsequently continuously drawn at a drawing speed of 400 m / min to obtain a 0.16 mm wire.

[0051] Comparative Example 1

[0052] A copper-chromium-zirconium alloy cast rod wire comprises 0.5wt% Cr, 0.05wt% Zr, and the balance is copper, and has a wire diameter of 16 mm. The reagents and process parameters used in the preparation method are the same as those in Example 1, except that no Cu5Mg intermediate alloy is added in step (1), and finally in step (2), when the pulling is performed by the "pulling + stopping + retreating" method, Figure 3 As shown in c, the cast rod has fracture.

[0053] Comparative Example 2

[0054] A copper-chromium-zirconium alloy casting rod comprises 0.5wt% Cr, 0.05wt% Zr, 0.05wt% Mg, and the balance is copper. The wire diameter is 16mm. The reagents and process parameters used in the preparation method are the same as those in steps (1) and (2) in Example 1. The difference is that in step (2), vacuum down-drawing continuous casting is carried out, the pressure is less than 0.1Pa, the cooling water and the air cooling device at the outlet of the traction pipe are turned on, the flow rate is 800L / h, the water tank temperature is maintained at 28±2℃, the traction system and the wire taking-up device are turned on, the whole process is carried out in a "pulling + withdrawing" manner, the pulling and withdrawing time ratio is 5:3, the pulling is carried out at a speed of 3mm / s for 100mm in the initial stage of traction, and then the pulling speed is increased to 5mm / s, and the withdrawing speed is maintained at 2mm / s. The copper liquid condenses into a solid in the graphite crystallizer, and thermal cracking occurs during traction, resulting in traction failure.

[0055] Comparative Example 3

[0056] A copper-chromium-zirconium alloy wire comprises 0.5wt% Cr, 0.05wt% Zr, 0.05wt% Mg, the remainder being copper, and a wire diameter of 0.16mm. The reagents and process parameters used in the preparation method are the same as those in Example 1, except that in step (2), vacuum down-drawing continuous casting is performed, the pressure is less than 0.1Pa, the cooling water and the air cooling device at the outlet of the traction pipe are turned on, the flow rate is 800L / h, the water tank temperature is maintained at 28±2°C, the traction system and the wire-receiving device are turned on, the whole process is carried out in a "traction+stop+retreat" manner, the stop time is 0.1s, the stop-pull time ratio of the whole process of "traction+stop+retreat" is controlled at 1:1, and the stop-retreat time ratio is 2:1. In the initial stage of traction, 100mm is pulled at a speed of 5mm / s, and then the traction speed is increased to 9mm / s, and the retreat speed is maintained at 2mm / s. The copper liquid condenses into a solid in a graphite crystallizer, and the traction is stable until the traction is completed, so as to obtain a cast rod with a wire diameter of 16mm without thermal cracking or fracture.

[0057] Performance testing

[0058] 1. The cast rod broken by traction in step (2) of comparative example 1 and the alloy cast rod obtained in step (2) of example 1 were tested. Figure 3As shown in ab, by comparison, it is found that the addition of trace Mg elements in Example 1 reduces the grain size of the cast rod, making the cast rod structure more uniform, and obtaining a structure with a relatively uniform distribution and an average grain size close to 6 mm.

[0059] 2. According to the national standard GB / T 34505-2017 "Room Temperature Tensile Test Method for Copper and Copper Alloy Materials", the tensile strength and elongation of the wires prepared in the embodiments and comparative examples were tested. The tensile test was tested using an RGM-6005 microcomputer-controlled electronic universal testing machine, the tensile rate was selected to be 10 mm / min, and the wire drawing was verified by an LW-100-26YD wire drawing machine. According to actual production requirements, wire drawing of more than 1500m without breaking the wire can be carried out for subsequent processing and is considered qualified. The test results are shown in Table 1 below.

[0060] 3. According to the national standard GB / T 351-2019 "Method for measuring the resistivity of metal materials", the wires prepared in the embodiments and comparative examples were subjected to conductivity tests, wherein the conductivity was tested using a TXJ-300 intelligent metal conductor conductivity meter. The test results are shown in Table 1 below.

[0061] 4. Average grain size: According to the national standard GB / T 3488.2-2018 "Metallographic determination of cemented carbide microstructure", the grain size of the cast rod prepared in step (2) of the embodiment and the comparative example was detected by laser confocal microscopy. The detection results are shown in Table 1 below.

[0062] Table 1 - Performance test results of alloy wires prepared in the present application examples and comparative examples

[0063]

[0064] like Figure 3 As shown in cd, the cast rod prepared by the copper-chromium-zirconium alloy in Example 1 of the present application has a lower grain size, a uniform cast rod structure, and the copper liquid is added with Cu5Mg intermediate alloy, which helps to improve viscosity and reduce the resistance of the downward continuous casting. The copper liquid is pulled into a solid in the graphite crystallizer by the "pull + stop + retreat" method. The cast rod does not have thermal cracking or fracture, has good mechanical properties and processability, and is not prone to wire breakage during the subsequent drawing process. The tensile strength, elongation and conductivity of the prepared wire are all high. In Comparative Example 1, the cast rod is not added with Cu5Mg intermediate alloy, the viscosity of the copper liquid is high, and the resistance is large, resulting in the fracture of the cast rod during the traction process, affecting the subsequent processing, and the grain size of the cast rod is significantly increased. In Comparative Example 2, the cast rod is prepared by the "pull + retreat" method, resulting in obvious thermal cracking on the surface of the cast rod, which affects the subsequent traction.

[0065] As shown in Table 1, during the traction process of the cast rod in the "pull + stop + retreat" mode in Example 1 of the present application, the speed and time ratio of traction, retreat and stop are controlled, which can avoid breakage and reduce thermal cracking. The grain size formed in the cast rod during the cooling process is small, the mechanical properties of the cast rod are high, and the tensile strength and elongation of the wire after drawing are high, which is beneficial to improving the performance of the wire.

[0066] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. It is particularly pointed out that for those skilled in the art, any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a high-performance copper-chromium-zirconium alloy casting rod, characterized in that: The alloy casting rod comprises 0.2wt%-1.5wt% Cr, 0.02wt%-0.15wt% Zr and 0.01wt%-0.05wt% R, and the balance is copper and unavoidable impurities, wherein R is an element such as Mg and / or Zn, and the preparation method thereof comprises the following steps: (1) Under inert gas atmosphere, after the cathode copper, copper-chromium master alloy and copper-zirconium master alloy are melted, copper-magnesium master alloy and / or copper-zinc master alloy are added, and after they are completely melted, electromagnetic stirring is performed, a covering agent is added, and the copper liquid is heat-insulated; (2) Carry out vacuum continuous casting, turn on the cooling water and air cooling device at the outlet of the traction pipe, turn on the traction system and the wire-retracting device, and the whole process is carried out in the manner of "traction + stop + retreat". The stop time is 0.1-0.2s, the ratio of the stop-pull time is more than 3:1, and the ratio of the stop-retreat time is more than 5:

1. In the initial stage, the traction speed is 3mm / s for 50-200mm, and then it is increased to 5-7mm / s for traction. The retreat speed is kept unchanged at 2mm / s. The copper liquid condenses into a solid in the crystallizer, and the traction is stable until the traction is completed to obtain a cast rod.

2. The method for preparing a high-performance copper-chromium-zirconium alloy casting rod according to claim 1, characterized in that: In step (1), under inert gas atmosphere, cathode copper is added and melted at above 1050° C., then inert gas protection is introduced, copper-chromium master alloy is added, the temperature is raised to 1150-1250° C., copper-zirconium master alloy is added, the temperature is raised to 1250-1350° C., copper-magnesium master alloy and / or copper-zinc master alloy are added, electromagnetic stirring is performed after complete melting, a covering agent is added, and the temperature is kept at 1200-1300° C. for 10-30 minutes.

3. The method for preparing a high performance copper-chromium-zirconium alloy casting rod according to claim 1, characterized in that: In step (1), the covering agent is cryolite.

4. The method for preparing a high performance copper-chromium-zirconium alloy casting rod according to claim 1, characterized in that: In step (2), the crucible and crystallizer used for vacuum continuous casting are independent of each other and are internally sprayed with boron nitride coating, embedded with 5-10 mm boron nitride or embedded with 5-10 mm high-purity molybdenum-titanium alloy.

5. The method for preparing a high performance copper-chromium-zirconium alloy casting rod according to claim 1, characterized in that: In step (2), the diameter of the graphite crystallizer is 12.5-16 mm.

6. The method for preparing a high performance copper-chromium-zirconium alloy casting rod according to claim 1, characterized in that: In step (2), the water flow rate of the cooling device is 500-4000 L / h, and the circulating water temperature is 25-30°C.

7. A high performance copper-chromium-zirconium alloy casting rod prepared by the method for preparing a high performance copper-chromium-zirconium alloy casting rod as claimed in any one of claims 1 to 6.

8. A method for preparing a high-performance copper-chromium-zirconium alloy wire, characterized in that: The high performance copper-chromium-zirconium alloy casting rod as claimed in claim 7 comprises the following steps: (1) continuously extruding the cast rod to 6-10 mm at an extrusion temperature of 600-800° C., and then continuously drawing the extruded rod for the first time to 2-4 mm at a drawing rate of 17-34 m / min to obtain a wire blank; (2) The wire blank is heat treated at a temperature of 450-600° C. After cooling, it is continuously drawn for a second time to 0.1-0.2 mm at a drawing speed of 300-500 m / min to obtain a wire.

9. The method for preparing a high-performance copper-chromium-zirconium alloy wire according to claim 8, characterized in that: In step (1), continuous extrusion is performed using a preheated pure copper rod as a lead, the preheating temperature of the pure copper extrusion lead is 350-500°C, the extrusion temperature is 600-800°C, the extrusion wheel speed is 6-10 rpm, and the gap between the extrusion wheel and the die cavity is controlled to be 0.3-0.6 mm.

10. A high performance copper-chromium-zirconium alloy wire prepared by the method for preparing a high performance copper-chromium-zirconium alloy wire as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • Copper-chromium-zirconium alloy contact wire and production technique thereof

    CN107739872A

  • Preparation method of copper-chromium-zirconium alloy wire

    CN110218898A

  • Preparation method of high-strength and high-conductivity copper-chromium-zirconium alloy

    CN115074564A

  • Copper-chromium-zirconium alloy cast ingot and preparation method and application thereof

    CN115679136A

  • Non-vacuum preparation method of copper-chromium-zirconium alloy bar wire blank

    CN118028642A